Theoretical preconditions of vocational training the future teacher of music (Pedagogy of Higher and Secondary Education, 2006)
In article mechanisms of preparation the future teacher of music to performing activity are analysed; stages of preparation for this activity are isolated; the contents of. a method ofauto-training is opened.
Keywords: vocational training; performing activity; dynamic structure of the person; auto-training